OPTIMIZING THE CONTENTS OF TRAINING FOR THE MEN'S REPRESENTATIVE VOLLEYBALL SCHOOL TEAM - UNGUREAN B.C; PUNI A.R. (Editura Universitatii Transilvania din Brasov, 2019)
The purpose of the paper was to select the most efficient means to acquire the technical and tactical procedures specific to volleyball, to explain and use them during the physical education class or the optional discipline, and the results obtained should prove their efficiency in attaining the goals. It may be asserted that training based on a judicious planning and on using in teaching modern acting system - selected and systematized following the model of competitive game - leads to a substantial increase in the level of manifestation of motor qualities during the game, as well as to the increase of game action acquisition, which ultimately reflects on the image of the game practice by the team. In this respect, the methodology used, the action systems and the means used must be administered in a logical sequence; they should be precisely dosed, quantified and highly efficient.